An efficient guanidinium isothiocyanate additive for improving the photovoltaic performances and thermal stability of perovskite solar cells. (20th November 2018) - Zou, Junjie; Liu, Weier; Deng, Wenqiu; Lei, Gui; Zeng, Shi; Xiong, Juan; Gu, Haoshuang; Hu, Zhenglong; Wang, Xianbao; Li, Jinhua
Abstract: Organometallic perovskites have recently emerged as excellent solar cell materials for high power conversion efficiencies owed to their remarkable absorber characteristics, easy processing and low cost. Many efforts have been made by choosing appropriate additives to improve the power conversion efficiency and the stability. In this work, guanidine thiocyanate as the additive is introduced into the lead precursor solution to prepare perovskite films via two-step solution method. It is found that guanidine thiocyanate additive can notably improve the power conversion efficiency and the stability of MAPbI3 perovskite solar cells due to the improvement of quality and crystal structure of perovskite films. After adding guanidine thiocyanate into lead precursor to prepare perovskite films, the high power conversion efficiency of solar cell is increased from 15.24% to 16.92%. The improvement mechanisms of power conversion efficiency and thermal stability of perovskite solar cells have been studied. Thiocyanate ion additive largely affects the immediate nucleation process of perovskite film in which provides the improved morphology of the perovskite film, while thiocyanate ions are absent from the resulting perovskite film. However, guanidine ion can substitute methylammonium ion in lattices of perovskite. The guanidine-ion additive is mainly responsible for the improvement of thermal stability of perovskite film and can increase the power conversion efficiency of solar cells. Graphical abstract: Highlights: An additive of GITC was first introduced into the precursor solution for improving the performances of MAPbI3 solar cells. Thiocyanate ion additive largely affects the immediate nucleation process of perovskite film the quality of perovskite film. Guanidine ion can substitute MA ion in lattices of perovskite film and improve the thermal stability of perovskite film. More efficient carrier extraction and better charge-transfer ability in perovskite solar cells with 5% GITC additive.